Letter : International Brigade Association - Child, H. E.
035-0040-001 SOUTHAMPTON TRADES COUNCIL 35 LYTHAM ROAD, BITTERNE PARK, SOUTHAMPTON Secretary H.E. CHILD Telephone SOUTHAMPTON 55982 Your Ref: RB/EMK/193. 12th November, 1950. Mr. R. Boyfield, Secretary, Organisation Department, Trades Union Congress, Transport House, Smith Square, London, S.W.1. Dear Mr. Boyfield, International Brigade Association. Thank you for your letter of the 2nd November in reply to my enquiry of the 31st October. I am obliged by your answer which was appreciably more clear and definite than your last reply to a question raised by my Council, but I don't understand why you thought that our Chairman should have ruled the correspondence from the International Brigade Association out of order. We had received no indication that the Association was a proscribed Organisation, and any question affecting the welfare of Spanish Republicans who oppose the Franco regime has always received our sympathetic consideration. Only as recently as June, 1949, we sent £54 to the T.U.C. for transmission to Spain, to assist the resistance movement inside Spain. Long before this, many of our members have worked hard to assist in varying ways the victims of the Fascist rebellion and more important still, two of our young townsmen lost their lives, fighting in Spain as members of the International Brigade. This latter fact was mentioned in our resolution to the French Embassy. In making the protest, we were not primarily concerned with the choice of destination offered but resented the fact of these anti-Fascist Spaniards being forcibly expelled from the country in which they had sought sanctuary as political refugees. Yours sincerely, H.E. Child, Secretary. 292/946/35/40